Telaah Unsur Delik Trading In Influence dalam Pembaharuan Hukum Pidana di Indonesia - Sheryn Lawrencya (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Trading in influence acts that are non-mandatory offences has been regulated in the UNCAC, ratified by Law Number 7 of 2006 concerning the Ratification of the UNCAC. Based on cases in Indonesia, the act of Trading in Influence has developed in Indonesia but is considered a